PS02.200: A COMPREHENSIVE SCREENING OF THE FRA-1 REGULATORY GENES IN ESOPHAGEAL SQUAMOUS CELL CARCINOMA. (14th September 2018) - Toyozumi, Takeshi; Hoshino, Isamu; Sakata, Haruhito; Murakami, Kentaro; Kano, Masayuki; Takahashi, Masahiko; Sekino, Nobufumi; Yokoyama, Masaya; Okada, Koichiro; Shiraishi, Tadashi; Matsubara, Hisahiro
Abstract: Background: The expression of Fos-related antigen 1 (Fra-1) affects tumor progression, migration and invasion. We previously reported that a high Fra-1 expression level is associated with lymph node metastasis and a poor prognosis in patients with esophageal squamous cell carcinoma (ESCC). In this study, we identified the genes regulated by Fra-1 in ESCC. Methods: We constructed Fra-1 knockdown models via the transfection of small interfering RNA (siRNA) into ESCC cell lines (TE10, TE11). The expression levels of the genes in the knockdown models were analyzed using a microarray experiment and Biobase Upstream Analysis (Cytoline Solutions, Tokyo, Japan), and candidate genes regulated by Fra-1 in the ESCC cell lines were detected. The actual connection of Fra-1 to the promoter region was identified in a ChIP-PCR experiment. The expression levels of the candidate genes regulated by Fra-1 in the primary tumors of surgical specimens obtained from ESCC patients (n = 135) were compared to those observed in normal tissues using real-time PCR and immunohistochemical staining, and the clinicopathological features were analyzed. Results: The results of the Biobase Upstream Analysis and ChIP-PCR showed high mobility group protein 1 (HMGA1) and hyaluronan mediated motility receptor (HMMR) to be significant genes regulated by Fra-1. The expression levels of both HMGA1 and HMMR were found to closely correlate with the Fra-1 expression in the clinical specimens. The patients with a positive HMGA1 expression had a poorer prognosis than those with a negative expression ( P  = 0.017) and the patients with positive HMMR expression also had a poorer prognosis ( P  = 0.018). Moreover, a multivariate analysis demonstrated a positive HMGA1 expression to be a significant independent prognostic factor in the ESCC patients. Conclusion: HMGA1 and HMMR are regulated by Fra-1 in the setting of ESCC and the HMGA1 expression is significantly associated with a poor prognosis in ESCC patients. Downregulating the HMGA1 and HMMR expression may become a practical treatment strategy against ESCC in the future. Disclosure: All authors have declared no conflicts of interest.